Dampak Pengajian Tastafi terhadap Perkembangan Aspek Psikoreligius Masyarakat Langsa - T. Wildan; Muhajir (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This research learns the level of Tastafi's recitation activities on changes in psycho-religious aspects of Langsa City community. The objective determines the community's motivation to participate in Tastafi's recitation activities and their impacts on development and changes in their psycho-religious aspects. The methodology combines between qualitative and quantitative approaches. The qualitative approach uses theory of religiously psychological, monistic and faculty. As for the quantitative approach use percentage theory and Pearson's product-moment. Data collection uses questionnaires, observations, and documentation techniques. The research subjects were 30 Langsa City residents as members of the Tastafi recitation. It was found that there was a significant change from the psycho-religious aspect. The Tastafi arrival changes the Langsa City people's behavior, such as increasing worship activities, religious spirit, knowledge practice, and spiritual values in daily life. The routine level in these Tastafi recitation activities is very high, up to 50% (15 people). Furthermore, the change in psycho-religious aspects after attending the recitation is 60% (18 people). The Pearson's product-moment calculation prove that the significance and correlation are positive (perfect) with a rxy value of 0.798.